IDL6‐HAE/HSL2 impacts pectin degradation and resistance to Pseudomonas syringae pv tomato DC3000 in Arabidopsis leaves. (16th January 2017) - Wang, Xin; Hou, Shuguo; Wu, Qiqi; Lin, Minyan; Acharya, Biswa R.; Wu, Daoji; Zhang, Wei
Summary: Plant cell walls undergo dynamic structural and chemical changes during plant development and growth. Floral organ abscission and lateral root emergence are both accompanied by cell‐wall remodeling, which involves the INFLORESCENCE DEFICIENT IN ABSCISSION (IDA)‐derived peptide and its receptors, HAESA (HAE) and HAESA‐LIKE2 (HSL2). Plant cell walls also act as barriers against pathogenic invaders. Thus, the cell‐wall remodeling during plant development could have an influence on plant resistance to phytopathogens. Here, we identified IDA ‐like 6 ( IDL6 ), a gene that is prominently expressed in Arabidopsis leaves. IDL6 expression in Arabidopsis leaves is significantly upregulated when the plant is suffering from attacks of the bacterial Pseudomonas syringae pv. tomato ( Pst ) DC3000. IDL6 overexpression and knockdown lines respectively decrease and increase the Arabidopsis resistance to Pst DC3000, indicating that the gene promotes the Arabidopsis susceptibility to Pst DC3000. Moreover, IDL6 promotes the expression of a polygalacturonase (PG) gene, ADPG2, and increases PG activity in Arabidopsis leaves, which in turn reduces leaf pectin content and leaf robustness. ADPG2 overexpression restrains Arabidopsis resistance to Pst DC3000, whereas ADPG2 loss‐of‐function mutants increase the resistance to the bacterium. Pst DC3000 infection elevates the ADPG2 expression partially through HAE and HSL2. Taken together, our results suggest that IDL6‐HAE/HSL2 facilitates the ingress of Pst DC3000 by promoting pectin degradation in Arabidopsis leaves, and Pst DC3000 might enhance its infection by manipulating the IDL6‐HAE/HSL2‐ADPG2 signaling pathway. Significance Statement: During floral abscission a peptide ligand (IDA) and receptor kinases HAESA and HAESA‐LIKE2 act together to promote the activity of cell wall degrading enzymes. Here we show that expression of an IDA‐like peptide, IDL6, is increased upon bacterial pathogen infection and that expression of cell wall degrading enzymes is consequently increased, thus facilitating pathogen entry.